Service Evaluation of Transition Pathway and Audit of National Institute of Clinical Excellence (NICE) Guidelines Compliance - Umama Khan; Basanta Sapkota; Parvathy Suresh; Amaia Del-Pozo-Ugalde; Jeremy Turk (BJPsych Open, 2025)
Aims: This project aimed to evaluate our transition service for young people, from Child & Adolescent Service (CAMHS) to Adult Mental Health Services (AMHS), and to audit NICE transition guidelines compliance.